Effects of glyphosate on the ovarian function of pregnant mice, the secretion of hormones and the sex ratio of their fetuses. (December 2018) - Ren, Xin; Li, Ruonan; Liu, Junze; Huang, Kai; Wu, Sheng; Li, Yansen; Li, Chunmei
Abstract: Glyphosate is the active ingredient of the commercial formulation Roundup®, which is used worldwide. This study aimed to investigate the toxic effects of pure glyphosate or Roundup® on pregnant mice and their fetuses during pregnancy. From gestation days (GDs) 1–19, ICR mice were orally administered distilled water, 0.5% glyphosate solution or 0.5%-glyphosate Roundup® solution. The ovaries and serum were collected at GD19. The results showed decreases in body weight gain and, ovary and liver weight in glyphosate-treated mice. Additionally, histopathological alterations in the ovary including increased atretic follicles, interstitial fibrosis and decreased mature follicles were observed in the groups treated with glyphosate. The serum concentrations of both progesterone and estrogen were markedly altered after glyphosate exposure, and there were also changes in the expression of GnRH, LHR, FSHR, 3β-HSD and Cyp19a1 genes at the hypothalamic-pituitary-ovarian axis. Furthermore, oxidative stress was observed in the treated mice, increasing the activity of T-AOC, CAT and GSH-Px, as well as the MDA content in both the serum and ovary. With regard to litters, the sex ratio was significantly altered by pure glyphosate. These results show that glyphosate is able to cause several effects on pregnant mice, such as ovarian failure, interference with hormone secretion by affecting the steroidogenesis-related gene expression, and oxidative stress. The sex ratio of litters was also influenced by prenatal exposure to pure glyphosate. Graphical abstract: Image 1 Highlights: Prenatal exposure to pure glyphosate affected sex ratios of litters. Glyphosate caused ovarian histopathological alterations in pregnant mice. Glyphosate disrupted the secretion of progesterone and estrogen in pregnant mice. Glyphosate disrupted expressions of steroidogenesis-related genes in pregnant mice. Glyphosate induced oxidative stress in ovary and serum of pregnant mice. Abstract : The ovarian failure and potential premature delivery induced by glyphosate should raise other researchers' concern about its toxicity to pregnant females.